Ekoparkernas inverkan på långhornskalbaggar (Cerambycidae) - Skogqvist, Elias; Andersson, Emil (2022)
Several dead wood-dependent beetles need substrates which to great extent have been disfavored by intense forestry. Active and continuous restoration in Ecoparks may offer an option with intention to improve the habitation conditions. This study investigated, with data from 2011 and 2020, if longhorn beetle species communities, abundance, species richness and red-listed occurrence were different in an Ecopark compared to a conventional production landscape as a reference. The hypothesis was that the species richness and abundance in general are higher in the Ecopark, and that the trend over time will indicate a sharper difference between Ecoparks and conventionally managed forest. Regarding species communities and red-listed species, the assumption was that the Ecopark over time will inhabit another species composition and more redlisted species compared to the conventionally managed forest. The assumptions are based on earlier studies showing that dead wood-dependent beetles are favored by nature conservation – in particular by creation of dead wood.